(untitled) - Kaplan, Harold I. (Baltimore, 1990)
Kaplan and Sadock's Pocket Handbook of Clinical Psychiatry remains a staple for medical students on psychiatric rotations, psychiatric residents, practitioners, and mental health professionals. In an easy-to-scan outline format, this popular quick-reference handbook summarizes the etiology, epidemiology, clinical characteristics, diagnosis, and treatment of all psychiatric disorders in adults and children.
Keywords: Psychiatry,Tâm thần